SIFAT ISOMORFIK PADA OPERASI TENSOR, BINTANG, CARTESIUS, DAN MODULAR DUA GRAF FUZZY - Triyani Triyani; Bambang Hendriya Guswanto; Nurhayati nurhayati (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2020)
This article discusses about some isomorphic properties of tensor, star, Cartesius, and modular product operations of two fuzzy graphs. The results of research are the tensor product of two fuzzy graphs is isomorphic, and if and are complete fuzzy graphs then , , and . Full Article